Perancangan Jaringan Femtocell Pada Jaringan 3G Di Gedung C Fakultas Teknik Universitas Riau - Akmal Akmal; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The worst network performance of “3” network provider at Building C, Faculty of Engineering has affected to the users in download / upload data from internet. Walking test measuremeat has performed and showed that average power level at each floor is -95,59 dBm. It does not meet 3GPP standard. Therefore, this paper presents the design of femtocell network for 3G indoor communication at Building C, Faculty of Engineering, University of Riau by using Radio Wave Propagation Simulator (RPS). There are two design considerations need to be calculated such as coverage area and network capacity. In terms of coverage area, four (4) Femtocell Access Points (FAPs) are required for each floor. However for netwok capacity, the FAPs are not distibuted equally for each floor, two (2) FAPs are required for 1st and 2nd floor, five (5) FAPs are required for 3rd floor. Three (3) scenarios for FAPs position are performed in this simulation; FAP is at the middle, corner, and random of ceiling. The best simulation results are obtained for random position which gives coverage area of -36.19 dBm and the lowest Signal Interference Ratio (SIR) of 1.50 dB. Both results meet the 3GPP standard.Keywords: HSDPA, Femtocell, Radio Wave Propagation Simulator, Propagation COST 231 Multi-Wall Model